The setting of advertising budgets - Corkindale, David; Kennedy, Sherril (Cranfield School of Management, 1974)
This report summaries the contributions made by economists, management scientists and practitioners to the understanding of how advertising budgets should be set. Each approach offers insights and guidance for certain circumstances and these are brought out in the report.